Ge−Fe Carbonyl Cluster Compounds: Ionic Liquids‐Based Synthesis, Structures, and Properties - Dr. Silke Wolf; Dr. Alexander Egeberg; Jens Treptow; Prof. Dr. Claus Feldmann (ChemistryOpen, 2021)
Abstract Nine Ge−Fe carbonyl cluster compounds are prepared via ionic liquids‐based synthesis. This includes the novel compounds [EMIm][Fe(CO)3I(GeI3)], [EHIm][Fe(CO)3I(GeI3)], [BMIm][GeI2{Fe(CO)4}2(μ‐I)][AlCl4]2, [GeI2{Fe(CO)4}2(μ‐I)][Fe(AlBr4)3], [BMIm]2[(FeI2)0.75{Fe(CO)2I(GeI3)2}2], and [EHIm][Fe(CO)4(GeI2)2Fe(CO)3GeI3] as well as the previously reported compounds (Fe(CO)4(GeI3)2, FeI4{GeI3Fe(CO)3}2, and Ge12{Fe(CO)3}8(μ‐I)4 (EMIm: 1‐ethyl‐3‐methylimidazolium, EHIm: 1‐ethylimidazolium, BMIm: 1‐butyl‐3‐methylimidazolium). With this series of compounds, a comparison of synthesis conditions and structural features is possible and, for instance, allows correlating the composition and structure of the respective Ge−Fe carbonyl cluster compounds with the type and acidity of the ionic liquid. With [EMIm][{GeI3}2Fe(CO)3I], moreover, we can exemplarily show the thermal decomposition as a single‐source precursor in the ionic liquid, resulting in bimetallic Ge−Fe nanoparticles with small size and narrow size distribution (7.0±1.4 nm).